The complex structure of GRL0617 and SARS-CoV-2 PLpro reveals a hot spot for antiviral drug discovery - Ziyang Fu (Nature Portfolio, 2021)
The SARS-CoV-2 papain-like protease (PLpro) is of interest as a drug target. Here, the authors identify GRL0617 as a PPI (protein–protein interaction) inhibitor of SARS-CoV-2 PLpro that inhibits its deISGylating activity and present the mechanism of action of the compound through the GRL0617-bound PLpro crystal structure and NMR studies.